2008
DOI: 10.1192/bjp.bp.107.044362
|View full text |Cite
|
Sign up to set email alerts
|

Quick recovery of orientation after magnetic seizure therapy for major depressive disorder

Abstract: Introduction Magnetic seizure therapy (MST), in which seizures are elicited with a high-frequency magnetic field, is under development as a new treatment for major depressive disorder. Its use may be justified if it produces the antidepressant effects of ECT, coupled with limited cognitive side effects. This pilot study reports shortened recovery times after MST compared with ECT as a preliminary step to evaluate the usefulness of a new 100Hz MST device. Methods We induced seizures with 100Hz magnetic transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 14 publications
3
66
0
3
Order By: Relevance
“…In addition to faster reorientation, Lisanby et al (2003a) found significantly superior acute cognitive performance after MST than ECT. Faster reorientation after MST compared with prior ECT treatments was reported as well (Kirov et al, 2008). Finally, Fitzgerald et al (2013) found no evidence of neurocognitive impairment with MST.…”
Section: Introductionmentioning
confidence: 88%
“…In addition to faster reorientation, Lisanby et al (2003a) found significantly superior acute cognitive performance after MST than ECT. Faster reorientation after MST compared with prior ECT treatments was reported as well (Kirov et al, 2008). Finally, Fitzgerald et al (2013) found no evidence of neurocognitive impairment with MST.…”
Section: Introductionmentioning
confidence: 88%
“…Kirov et al confirmed these differences after stimulation at 100 Hz. EEG characteristics during ECT were markedly different from the EEG recorded after MST (Kirov et al 2008). In 2013, Fitzgerald et al reported shorter motor seizures, a lesser amplitude in the ictal activity and much less postictal suppression.…”
Section: Neurophysiological and Seizure Characteristicsmentioning
confidence: 94%
“…After the development of high-dose MST (HD-MST) with higher frequencies at 100 Hz, Kirov and colleagues published the first report on shorter reorientation time after An overview on clinical aspects in magnetic seizure therapy MST compared to ECT and less postictal confusion (Kirov et al 2008). Some more studies have suggested a favorable cognitive side effects profile of MST compared to ECT.…”
Section: Cognitive Effectsmentioning
confidence: 95%
“…Though studies in humans are based on individual case reports or small (less than 20 participants) groups there is growing evidence that MST is associated with few subjective and objective cognitive side effects (Hoy & Fitzgerald, 2010b;Kayser et al, 2011;Kosel et al, 2003;Lisanby et al, 2003a;Lisanby et al, 2001b), as well as rapid recovery of orientation after treatment compared with ECT (Kirov et al, 2008;White et al, 2006). Though more studies are needed, the neuropsychological profi le is likely to be superior to ECT.…”
Section: What Are the Effects On Cognition?mentioning
confidence: 99%
“…Early development of MST identifi ed potential adverse effects and associated solutions: earplug were used to protect hearing (rTMS produces a loud clicking caused by the vibrating of the copper wires within the stimulating coil) and electroencephalographic electrodes were modifi ed (using MRI compatible EEG electrodes) to prevent heating and potential for scalp burns (Lisanby, 2002). Use of 100 Hz transcranial magnetic stimulation over the vertex, closest to the motor cortex, appears to be the most reliable method of seizure induction (seizures induced in 10 out of 11 patients in one study) (Kirov et al, 2008) and is now the most frequently used stimulation (Kayser et al, 2011).…”
Section: How Is Treatment Delivered?mentioning
confidence: 99%